Developing Business Growth Strategy and Generic Framework for Insurance, UK - Dwivedi, Rohit (2010)
UK insurance industry is the third largest in the world and plays a unique role in helping businesses and consumers against the risks. But like many industries, UK insurance sector has been affected by the financial crisis. The main reasons being the massive decline of the investment income in 2009 and also increase in the number of fraud claims. The growth of life insurance and pensions is much higher than that of general insurance, because of the intense price pressures in the general insurance sector.